Efektivitas Penggunaan Media Roda Perkalian Pintar dalam Meningkatkan Motivasi Belajar dan Penguasaan Konsep Perkalian di Kelas IV SD 106813 Amplas - Putri Marsya; Nisa Alfina Zahra; Fitri Handayani Br Siregar; Syahrial S (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to analyze the effectiveness of the Smart Multiplication Wheel media in improving motivation and understanding of the multiplication concept. The background of the problem is the low learning outcomes of fourth-grade students at SD Negeri 106813 Amplas due to less varied teaching methods. The research method used is a quantitative experiment with a pretest-posttest control group design involving 30 students. The results of the research show a significant increase in learning outcomes. The number of students who passed the Minimum Completeness Criteria (KKM) increased from 18 students (60%) in the pretest to 25 students (83.3%) in the posttest, an increase of 23.3%. There was a shift in the concentration of student scores from a lower interval to a higher interval after the use of the media. The Smart Multiplication Wheel media proved effective in enhancing students' motivation, active participation, and conceptual understanding, making the learning process more interactive and enjoyable.